STUDENTS’ DIFFICULTIES IN TRANSLATING NARRATIVE TEXT FROM ENGLISH INTO INDONESIA AT GRADE VIII OF SMP NEGERI 9 PEMATANGSIANTAR - Basariya Pasaribu; herman herman; David Togi Hutahaean (Acitya: Journal of Teaching and Education, 2020)
This research was intended to find out kinds of students difficulties in translating narrative text from English into Indonesia of SMP Negeri 9 Pematangsiantar. Therefore, the researcher formulated a question as the problem. As follows: “What are the students difficulties in translating narrative text from English into Indonesia of SMP Negeri 9 Pematangsiantar?” The researcher was used qualitative design. To answer the problem, the researcher used grade eight students of SMP Negeri 9 Pematangsiantar as the population and used 31 students as the sample, they were VIII-1. The instrument of the research of this research was narrative text. The data were collected by using record video of mobile phone then to be analyzed the result of students’ translation and correction. The research finding showed that students were difficulties in translating narrative text from English into Indonesia. The highest number of students’ difficulty is tense (32%). The second most difficulties faced by students is sentence (25,4%). The third difficulty is phrase (16,6%). The fourth is clause (15,4%). The fifth difficulty is attribute (8,2%). And the last is indefinite article (2,4%). It can be conclude that students have difficulties in translating narrative text from English into Indonesia is tense, not sentence, phrase, clause, attribute, and article indefinite.